2005
DOI: 10.1016/j.cmet.2005.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Control of lipid metabolism by phosphorylation-dependent degradation of the SREBP family of transcription factors by SCFFbw7

Abstract: The sterol regulatory element binding protein (SREBP) family of transcription factors controls cholesterol and lipid metabolism. The nuclear forms of these proteins are rapidly degraded by the ubiquitin-proteasome pathway, but the signals and factors required for this are unknown. Here, we identify a phosphodegron in SREBP1a that serves as a recognition motif for the SCF(Fbw7) ubiquitin ligase. Fbw7 interacts with nuclear SREBP1a and enhances its ubiquitination and degradation in a manner dependent on the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
376
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(409 citation statements)
references
References 32 publications
22
376
1
1
Order By: Relevance
“…Early observations indicated that SREBP1a is phosphorylated in vivo (14). Subsequently, it has been suggested that both SREBP1 and SREBP2 are phosphorylated by various protein kinases, both in vivo and in vitro (15)(16)(17). We were interested in mapping the major phosphorylated residues in SREBP1, especially those found in the Ser͞Thr͞Gly-rich C terminus of the mature protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early observations indicated that SREBP1a is phosphorylated in vivo (14). Subsequently, it has been suggested that both SREBP1 and SREBP2 are phosphorylated by various protein kinases, both in vivo and in vitro (15)(16)(17). We were interested in mapping the major phosphorylated residues in SREBP1, especially those found in the Ser͞Thr͞Gly-rich C terminus of the mature protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the C terminus of mature SREBP1 contains two PEST motifs, sequences that are usually found in unstable proteins. Phosphorylation of Ser and Thr residues within PEST motifs have been shown to regulate the degradation of a number of proteins (29), including SREBPs (15). The C terminus of mature SREBP1 contains a total of 19 Ser and Thr residues, and it will be important to determine which of these are phosphorylated and how these modifications affects the stability of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that insulin may be involved in the transcriptional activity of SREBP1c through other regulatory mechanisms. Recent studies indicate that glycogen synthase kinase-3 (GSK-3) could phosphorylate SREBP1c, resulting in its ubiquitination and proteasomal degradation [21]. Insulin is known to inhibit GSK-3 activity via PKB dependent phosphorylation [5].…”
Section: Discussionmentioning
confidence: 99%
“…Sequences recognized by Fbxw7 in c-Myc, c-Jun and SREBP1a or -1c are phosphorylated by glycogen synthase kinase-3b (GSK-3b), resulting in the ubiquitylation and degradation of these proteins (Welcker et al, 2004;Yada et al, 2004;Sundqvist et al, 2005;Wei et al, 2005). NICD1 is also phosphorylated by GSK-3b.…”
Section: Discussionmentioning
confidence: 99%